2011
DOI: 10.1186/1472-6963-11-s2-s4
|View full text |Cite
|
Sign up to set email alerts
|

Devolution and public perceptions and experience of health services in Pakistan: linked cross sectional surveys in 2002 and 2004

Abstract: BackgroundThe government of Pakistan introduced devolution in 2001. Responsibility for delivery of most health services passed from provincial to district governments. Two national surveys examined public opinions, use, and experience of health services in 2001 and 2004, to assess the impact of devolution on these services from the point of view of the public.MethodsA stratified random cluster sample drawn in 2001 and revisited in 2004 included households in all districts. Field teams administered a questionna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…Our findings on perception of medical trainees towards devolution of healthcare concur with other studies that have reported on this matter [ 10 ]. There is clearly an apathetic attitude towards the devolution process from the students’ standpoint.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings on perception of medical trainees towards devolution of healthcare concur with other studies that have reported on this matter [ 10 ]. There is clearly an apathetic attitude towards the devolution process from the students’ standpoint.…”
Section: Discussionsupporting
confidence: 92%
“…A study in 2007 found that about two-thirds of care-seekers consulted village doctors first [ 34 ]. This preference for seeking health care from non-government providers is not confined to Bangladesh [ 25 , 35 - 38 ] and there is ongoing debate about the role of the private sector in health care in developing countries [ 39 , 40 ]. The very high use of unqualified practitioners of Western medicine is striking in Bangladesh.…”
Section: Discussionmentioning
confidence: 99%
“…Local governance ordinance established the district health system, transferring responsibility of service planning, provision, monitoring and evaluation from provincial to district levels (32,33). While district coordination officers established EPI targets, human resource and bridge financing was under provincial purview, causing conflicts in programme prioritization and financing (34).…”
Section: Programme Structure and Managementmentioning
confidence: 99%